Sequencing and assembly of small RNAs reveal the presence of several begomoviruses, potyviruses, badnaviruses and mastreviruses in the sweet potato leaf virome in Barbados - Alleyne, A.T.; Cummins, C.; Rowe, K.; James, M.; Fuentes, S.; Gutiérrez, D. (Springer, 2019)
Sweet potato [Ipomoea batatas (L.) Lam] is increasingly becoming an important food and industrial crop worldwide that is affected by over thirty viruses belonging to different virus families. Little is known about these viruses on the many local and commercial sweet potato cultivars in the Caribbean, including Barbados. Therefore, polymerase chain reaction (PCR) and small RNA sequencing and assembly (sRSA) were used to detect viruses in the sweet potato leaf virome in Barbados. The viruses detected by sRSA were mainly from two virus families in sweet potato: Geminiviridae (genus Begomovirus) and Caulimoviridae (genus Badnavirus). Together, these viruses accounted for more than 75% of the virus contigs found in the sweet potato leaf virome in Barbados. Although sweet potato feathery mottle virus (SPFMV, genus Potyvirus, family Potyviridae) was frequently detected by PCR in infected leaf samples, only 10% of the sequenced contigs matched to these viruses in the leaf virome. The results suggest the absence of the sweet potato virus disease complex (SPVD) in Barbados but reveal possibly new, severe single virus infections or emerging virus associations in the virome largely composed of begomoviruses, badnaviruses, potyviruses and mastreviruses previously unreported in sweet potato in the Caribbean.